Conflict and crime. Restorative justice in Italy - Palermo, Giovanna (Frontiers in Sociology, 2023)
The article presents a socio-legal analysis of the Legislative Decree (Lgs.D.) of 10 October 2022, n.150, implementing the law of 27 September 2021, n.134 (so-called “Cartabia reform”), which provides for the introduction in Italy of a comprehensive framework regulation of restorative justice. The central theme of this paper is precisely the conflict connected to a crime, the offender-victim relationship and restorative justice in the light of the aforementioned decree. As Luhmann observes, the omnipresence of conflicts in society is self-evident. Even the crime produces a conflict or, at times, is the extreme expression of a pre-existing and sometimes latent conflict. The problem that arises is, therefore, that of the control and management of conflicts. These are usually managed by the law, but, given its limitations, it is increasingly necessary to encourage the use of restorative justice programs. On an interpersonal level, conflict triggers a negative mechanism of hostility and disavowal of the other, which either wraps itself in an explosive vortex, or deviates, becoming the pretext for abandoning the only form of communication that conflict makes possible, as Luhmann observes, the one based on “no”. The Italian regulatory intervention certainly appears relevant, albeit with some critical issues, and to be kept under observation for future application developments.